The Awareness and Experience About Endoscopic Adverse Events Among South Korean Endoscopists - Oh, Eun Hye; Park, Junseok; Lee, Jun Kyu; Shin, Jeong Eun; Cho, Sangjin; Yoon, Seung Bae; Cho, Young Sin; Kwon, Yogn Hwan; Kim, Ki Bae; Kim, Wan Jung; Paik, Chang Nyol; Lim, Hyun Chul; et al. (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The number of endoscopic procedures and related adverse events is increasing. We investigated South Korean endoscopists’ awareness and experience of endoscopic adverse events. Materials and Methods: We used Google Forms to conduct an online questionnaire survey among South Korean endoscopists from December 11 to 29, 2020. The survey comprised 30 questions developed by members of the Quality Management Committee of the Korean Society of Gastrointestinal Endoscopy. Results: In total, 475 endoscopists participated in the survey. Of these, 454 (95.6%) were board-certified gastroenterologists and 255 (53.7%) had >10 years of endoscopy experience. Most participants had experienced serious adverse events requiring hospitalization (80.4%, 382/475); however, only 100 (21.1%) were aware of programs for the prevention and management of adverse endoscopic events in their affiliated endoscopy centers. Most participants (98.5%, 468/475) agreed with the need for education on medical accidents for healthcare workers. Responses were inconsistent regarding the definition of adverse events formulated by the 2010 American Society for Gastrointestinal Endoscopy Workshop. Most participants were not aware of the minimal standard terminology (76.6%, 364/475) and had not used it when writing endoscopy reports (88.8%, 422/475). Responses were inconsistent regarding which events to record in endoscopy records. Conclusion: Further discussion on the nationwide adverse-event reporting system and education program for adverse events related to endoscopy is needed to ensure the safety of patients and endoscopists.